Frameless Robot-Assisted vs Frame-Based Awake Deep Brain Stimulation Surgery: An Evaluation of Technique and New Challenges. Issue 3 (6th March 2022) - Fenoy, Albert J.; Conner, Christopher R.
Abstract : BACKGROUND: Methodological approaches to deep brain stimulation (DBS) continue to evolve from awake frame-based to asleep frameless procedures with robotic assistance, primarily directed to optimize operative efficiency, lead accuracy, and patient comfort. Comparison between the 2 is scarce. OBJECTIVE: To analyze the impacts of methodological differences on operative efficiency and stereotactic accuracy using a frame compared with a frameless robotic platform while maintaining the awake state and use of multiple microelectrode recording (MER) trajectories. METHODS: Thirty-four consecutive patients who underwent bilateral awake frameless robot-assisted DBS were compared with a previous cohort of 30 patients who underwent frame-based surgery. Patient demographics, operative times, and MER data were collected for both cohorts. Two-dimensional radial errors of lead placements were calculated. RESULTS: Preoperative setup, surgical, and total operating room times were all significantly greater for the robot-assisted cohort ( P < .001). The need for computed tomography imaging when referencing the robotic fiducials led to increased setup duration because of patient transport, unnecessary for the frame-based cohort. Multiple simultaneous MER trajectories increased surgical time (mean 26 min) for the robot-assisted cohort only. The mean radial errors in the robot-assisted and frame cohorts were 0.98 ± 0.66 and 0.74 ± 0.49 mm ( P = .03), respectively. CONCLUSION: The use of a truly frameless robotic platform such as the Mazor Renaissance (Mazor Robotics Ltd) presented challenges when implementing techniques used during awake frame-based surgery. Maintaining good accuracy, intraoperative reference imaging, and limited MER trajectories will help integrate frameless robot assistance into the awake DBS surgical workflow.